Molecular assessment of pitviper populations (genus trimeresurus) in Laos and Vietnam reveals new country record and overlooked diversity - Thi Hanh, Ngo; Quang Truong, Nguyen; Minh Hanh, Nguyen Vu; Quang Vinh, Luu; Phimphasone, Vilay; Van Nghia, Ha; Ziegler, Thomas; Le, Minh Duc (Vietnam Journal of Biotechnology, 2022)
Vietnam is home to at least ten species of the genus Trimeresurus (Asian green pitvipers) and at minimum five members are found in Laos. The number has been increasing in recent years because of new species descriptions, e.g., Trimeresurus guoi, and new records of recently discovered taxa, such as T. cardamomensis. However, the genus has still been poorly studied in Laos and Vietnam as many areas in the two countries have not been sufficiently surveyed. In addition, the taxonomic status of several populations in the two countries has not been thoroughly investigated. In this study, we sequenced 18 new samples of the Asian green pitvipers collected from various sites in Vietnam and from Khammouane province in Laos. Our analyses based on a short fragment of the mitochondrial COI gene confirm the occurrence of T. stejnegeri in Laos and thus increase the species richness in the country to at least six, but more study needs to be undertaken to better understand the diversity of the species group. Two other populations from Khammouane province potentially constitute cryptic species, although further investigation is warranted. In Vietnam, T. albolabris is broadly distributed and divided into two clades with unknown taxonomic status. Moreover, T. gumprechti is discovered in two new localities from the Northeastern provinces of Bac Giang and Cao Bang. It is apparent that this species might represent a species complex, which requires more detailed taxonomic treatment.